The role of community in youth offender panels in England and Wales - Cruz da Fonseca Rosenblatt, F (2013)
The primary aim of this thesis is to reach a better empirical and theoretical understanding of what ‘community involvement’ means and what work it does in restorative justice. A case study approach was adopted to examine the involvement of the community in one selected practice of restorative justice, namely youth offender panels in England and Wales. Data collection comprised 127 interviews with key stakeholders involved in youth offender panels, as well as observation of 39 panel meetings, and analysis of related documents (e.g. panel reports and contracts). The role of ‘community’ in youth offender panels is argued to be more ‘theatrical’ (or rhetorical) than real: community panel members do not have a real say in the type or extent of reparation the offender should undergo, they do not clearly benefit from this reparation, and they do not support the reintegration of offenders into the community. The experience of youth offender panels suggests that the greater involvement of lay members of the community – or their changing role from mere witnesses/juries to facilitators – does not help to fully incorporate community harm into criminal justice practice. The English and Welsh experience also suggests that restorative justice advocates have placed unreasonably high expectations on the benefits of lay involvement. For example, this study found that lay members of the community do not have better ‘local knowledge’ than professionals. All in all, a key lesson from the experience of youth offender panels is that – while ignoring the kind of community that features in contemporary, urban contexts – restorative justice programmes run the risk of paying lip service to genuine community involvement. In conclusion, it is argued that restorative justice programmes need to start from a more concrete and up-to-date notion of community. While operationalizing community involvement, they need to acknowledge, all at once: the importance of place; the importance of family links, friendship and other social ties; and the importance of similar social traits and identities.